Contribution of Learning Motivation and Stress on Academic Achievement of Medical Faculty Students - Yogie, Yogie; Suryadi, Suryadi; Soefijanto, Totok Amin (LPPM Undiksha, 2021)
The pressure and burden of studying in the medical faculty is greater than other majors because of the high pass mark requirements which cause stress. The adaptation process for students is difficult and the medical department is not a passion, instead the demands of parents make low achievement motivation which has an impact on decreased academic achievement. The purpose of this study was to determine the contribution of achievement motivation and stress to the academic achievement. This study uses a quantitative approach using survey methods and path analysis techniques. The research instrument was a closed questionnaire on google form based on the Likert scale. Hypothesis testing is obtained from the t test and F test. Hypothesis testing of this study uses Path Analysis with the help of the SPSS Version 20.0 application. The survey method involves collecting data to test hypotheses or answer people's questions about certain topics or problems. The number of research samples was 64 international class students. Sampling in this study using the Proportionate Stratified Random Sampling technique. This is because the population is not homogeneous. The finding of the results of this study is that achievement motivation has a positive contribution to academic achievement. Stress has a negative contribution to academic achievement. Achievement motivation has a negative contribution to stress.